Power/Knowledge Conflict while Introducing Cloud Computing into Manufacturing Companies in Poland – Research Outcomes - Magdalena ZALEWSKA-TURZYNSKA (Communications of International Proceedings, 2021)
Organizations need to adapt to changes taking place in the environment – it is an inevitable necessity. Introducing cloud computing (CC) to the company’s daily routine is one of possible adjustment in the field. However, such change is of technological nature, not the organizational one, therefore it may be assumed that a conflict among employees should not occur if changes touch only technological issues. The aim of this paper is to diagnose if conflicts occur at all while introducing cloud computing into manufacturing companies, and if yes, then – based on Foucauldian typology – what is the conflict origin: knowledge or power. The research form was quantitative (CATI and CAWI questionnaire) and it was applied to 400 companies twice in 2017-2018 and in 2020. Companies were chosen by set of strictly specified criteria’s, that was: companies having the office registered in the territory of the Republic of Poland and/or a production plant located there, companies representing only manufacturing sector, use of clouds on a regular basis (ether the mailing and office purposes or in wider range of applications). Moreover the size of companies were important – a sample were altogether 400 companies but at least 50 organizations from each group size: micro (employing up to 9 persons), small (10-49 people), medium (50-249 employees) and large (employment above 250). The research outcomes confirmed conflicts occurrence. They arose at most in 2020 in medium size companies, and knowledge origin conflicts outweigh power ones. The micro, small and large companies dealt and managed with conflicts better.
Keywords: Power Conflicts; Knowledge Conflicts; Cloud Computing; Manufacturing Companies.